#TITLE_ALTERNATIVE# - ADE SUGIAWATI (NIM : 20513030) , VINSENSIA
Nowadays, catalyst plays an important role in industry field. A lot of industrial products are produced from chemical process using catalyst. To date, ZSM-5 zeolite become as one type of catalyst is extensively used due to its high acid strength. ZSM-5 catalyst is used for many processes such as dehydration, isomerization, polymerization, cracking, alkylation, and so on. Conventionally, synthesis of zeolite ZSM-5 using organic compound as Structure Directing Agent is usually based on quaternary ammonium cation such as TPABr (Tetra propyl ammonium bromide) and TPAOH Tetra propyl ammonium hydroxide). Nevertheless, this zeolite synthesis’ technique is supposed not environmentallyfriendly and high-cost production. That’s why to overcome this problem, synthesis zeolite ZSM-5 without the using of SDA and seeds become a promising technique to prevent these drawbacks. In this research, zeolite ZSM-5 (MFI framework) was synthesized by hydrothermal method without using SDA and seeds. The precursors in this experiment are Cab-O-Sil, NaOH, Al(OH)3 and water. Zeolite structure was determined by XRD technique. Pore analysis was obtained by measurement of isothermal adsorption-desorption N2 curve. Crystal morphology was observed by using Scanning Electron Microscope, SEM. Synthesis ZSM-5 with molar compositions Si/Al = 25; NaOH/Si = 0,23; H2O/Si = 20 at 150 °C for 96 hours produce hexagonal prismatic morphology (coffin type) and magadite (cabbage like aggregates). By other variation of molar composition Si/Al = 25, NaOH/Si = 0,23; H2O/Si = 20 at 175 °C, ZSM-5 synthesized showed low cristallinity and other phase like mordenite still exist. The optimization by tumbling was done to produce high cristallinity of ZSM-5. Analysis of BET (Brunauer–Emmett–Teller) and NLDFT (Non Localized Density Functional Theory) were employed also to know the surface area of ZSM-5. Surface area, pore volume, and pore diameter based on analysis results were 223 m2/g, 0,148 cm3/g, and 3,8 nm, respectively. Hence, it can be concluded that ZSM-5 synthesized has mesopore.